pSESYNTH project: Community mobilization for a multi-disciplinary paleo database of the Global South - Kulkarni, Charuta (2023)
How to enhance paleoscientific research, collaboration and application in the Global South? The INQUA-funded multi-year pSESYNTH project envisions the first multi-disciplinary Holocene paleo database through a collaborative vision for past human–environmental systems in the Global South, and their future sustainability.